Neo-liberalism, the WTO and New Modes of Agri-environmental Governance in the European Union, the USA and Australia - Tilzey, Mark (The International Journal of Sociology of Agriculture and Food, 2021)
Neo-liberalism in agricultural policy has exhibited a growing presence in the ‘new global economy’, pursuing an agenda that seeks to dismantle the welfare components of established ‘national’ policies and to re-construct in their stead a new ‘post-Fordist’ accumulation dynamic and novel structures of governance simultaneously at regional and global levels. The WTO constitutes a key site for the re-regulation of international governance in favour of neo-liberalism, a process in which state intervention to underwrite agricultural production and environmental and social protection is deemed increasingly inadmissible where market ‘distortion’ is implied. Nevertheless, the implantation of neo-liberalism in agricultural policy exhibits considerable unevenness between states, being characterised by varying levels of accommodation and resistance. States appear to be seeking accumulation opportunities through liberalisation whilst simultaneously, and in varying degrees, striving to sustain some level of agricultural and socio-environmental ‘exceptionalism’ in policy, often manifested in new modes of agri-environmental governance. The nature and causal bases for these new modes of ‘post-Fordist’ governance are explored with reference to the European Union, the USA and Australia.